Process-based indicators to assess storm induced coastal hazards - Ferreira, Óscar (2019)
Storms are responsible for several hazards (e.g. overwash, erosion, inundation) in coastal areas, leading to the destruction of property and loss of life in populated areas. Various indicators are used to express potential storm impact and describe the associated hazards. The most commonly used indicators include either forcing parameters (e.g. wave height, sea level) or coastal morphologies (e.g. dune height or berm width). Whereas they do not represent the processes associated with storm induced hazards in coastal areas. Alternatively, a hazard could be better characterised if process-based indicators are used instead. Process-based indicators express the result of the forcing mechanisms acting over the coastal morphology and reflect both hydrodynamic and morphological characteristics. This work discusses and synthesizes the most relevant process-based indicators for sandy shores subject to overwash, erosion and inundation promoted by storms. Those include: overwash depth, potential and extent; shoreline, berm or dune retreat; vertical erosion; and inundation depth and extent. The selection of a reduced set of process-based indicators to identify coastal hazards induced by storms in sandy coasts will facilitate comparison of different coastal behaviours for distinct storm return periods, and help to optimise coastal management plans, thereby contributing to the reduction of coastal risks.